2019
DOI: 10.1016/j.echo.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Dysfunction by Myocardial Contrast Echocardiography in Nonelderly Patients Referred for Computed Tomographic Coronary Angiography

Abstract: BACKGROUND-Microvascular dysfunction (MVD) is a potential cause of chest pain in younger individuals. We hypothesized that non-elderly patients referred for computed tomography coronary angiography (CTA) but without significant stenosis would have a high prevalence of MVD by myocardial contrast echocardiography (MCE). Secondary aims were to test whether the presence of non-obstructive CAD or reduced brachial flow-mediated dilation (FMD) predicted MVD. METHODS-Subjects ≤60 years-of-age undergoing CTA were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…MBF reserve assessed during hyperaemic echocardiography has been shown to be associated with the severity of coronary stenosis in patients with stable angina 118 . In a meta-analysis, MBF reserve had high accuracy for the prediction of flow-limiting coronary artery disease 118 and could be used to determine the pathophysiological basis of microcirculatory angina 127 .…”
Section: Echocardiographymentioning
confidence: 99%
“…MBF reserve assessed during hyperaemic echocardiography has been shown to be associated with the severity of coronary stenosis in patients with stable angina 118 . In a meta-analysis, MBF reserve had high accuracy for the prediction of flow-limiting coronary artery disease 118 and could be used to determine the pathophysiological basis of microcirculatory angina 127 .…”
Section: Echocardiographymentioning
confidence: 99%
“…Furthermore, during this systematic review, we found several other imaging modalities that are studied for their potential to diagnose CMD, such as myocardial contrast echocardiography (MCE) [ 63 , 75 , 76 ], CT-perfusion [ 77 ] and absolute quantification of myocardial perfusion by CMR [ 78 ]. Even though, current evidence is still limited so the clinical significance and applicability in regular care of these modalities in CMD diagnosis remains unclear, current research shows promising results.…”
Section: Discussionmentioning
confidence: 99%
“…This method relies on the acoustic signal produced by microbubbles as they transit through the coronary microcirculation and provides key information on perfusion, including the blood microvascular flux rate and functional patency of the microcirculation (microvascular blood volume). 5,6 MCE was performed Submitted 11 June 2020; accepted 3 August 2020; published online 1 September 2020. DOI 10.1182/bloodadvances.2020002644.…”
Section: Methodsmentioning
confidence: 99%